Pengaruh nilai ujian nasional, kedisiplinan, dan motivasi belajar terhadap hasil belajar bahasa Indonesia siswa SMP di Kecamatan Pandak - Purwanti, Sri; Pardimin, Pardimin (Bulletin of Educational Management and Innovation, 2024)
Background: Indonesian as a subject is not only important in academic aspects, but also plays a role that is influenced by external and internal factors, external factors such as National Examination scores, internal factors such as discipline and motivation to learn. Purpose: This study was conducted to determine the influence of the Indonesian Language National Examination Score, discipline, and learning motivation on the learning outcomes of Indonesian Language students in junior high schools throughout Pandak District. Method: The research is survey research with cross-sectional method. The population in this study were 658 grade VIII junior high school students in Pandak District, including SMP Negeri 1 Pandak, SMP Negeri 2 Pandak, SMP Negeri 3 Pandak, SMP Negeri 4 Pandak, and SMP "17" Pandak, while the research sample consisted of 228 respondents determined using proportional random sampling. The data analysis used was multiple linear regression analysis. Findings: The results of the multiple linear regression test found that variable X1 had a positive and significant partial effect on variable Y, based on rxy (0.325). Variable X2 had a positive and significant partial effect on variable Y based on the rxy value (0.206). Variable X3 had a positive and significant partial effect on variable Y based on the rxy value (0.211). The Indonesian National Examination Score, discipline, and learning motivation have a positive and significant effect simultaneously on the learning outcomes of Indonesian language in junior high schools in Pandak District, Bantul, Special Region of Yogyakarta based on the F count value (14, 558). The form of influence is positive, namely there is a tendency that is directly proportional between the independent variables and the dependent variables.